Succulents simplified : growing, designing, and crafting with 100 easy-care varieties - Baldwin, Debra Lee (Timber Press, 2013)
A complete primer on choosing, growing and designing with succulents. Along with gorgeous photos packed with design ideas, Debra offers her top 100 plant picks and explains how to grow and care for succulents no matter where you live. Step-by-step projects, including a cake-stand centerpiece, special-occasion bouquets, a vertical garden, and a succulent topiary sphere, will inspire you to express your individual style. --Publishers Description.